Pengaruh Belanja Pemerintah Terhadap Pertumbuhan Ekonomi di Provinsi Kalimantan Timur Menurut Perspektif Ekonomi Islam Tahun 2018-2024 - Shinta Riana Putri; Liya Ermawati; Zathu Restie Utamie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Local governments play a role in driving economic growth through local spending policies. East Kalimantan Province, as a region dominated by the mining sector, faces challenges in maintaining the stability of economic growth due to global economic fluctuations. Therefore, this study aims to analyze the impact of government spending including personnel expenditures, goods and services expenditures, and capital expenditures on economic growth in East Kalimantan Province from 2018 to 2024 from an Islamic economic perspective. This is an associative-causal study employing a quantitative approach. The data used are secondary data obtained from the Central Statistics Agency (BPS), the Ministry of Finance of the Republic of Indonesia, and the Directorate General of Fiscal Balance (DJPK). The data were analyzed using panel data regression analysis. The number of observations used is 70, obtained from 7 regencies and 3 cities in East Kalimantan over the period 2018–2024. The results of the model selection tests the Chow test and the Hausman test indicate that the selected model is the Random Effects Model (REM). The results of the partial analysis indicate that the personnel expenditure variable has a probability value of 0.2437 > 0.05, meaning that, in isolation, personnel expenditure does not have a significant effect on economic growth. Furthermore, the goods and services expenditure variable shows a probability value of 0.3194 > 0.05, meaning that goods and services expenditure also does not have a significant effect on economic growth. As for capital expenditure, it shows a probability value of 0.0849 > 0.05, indicating that capital expenditure also does not have a significant effect on economic growth in East Kalimantan. Meanwhile, simultaneously, personnel expenditure, goods and services expenditure, and capital expenditure have an effect on economic growth with a probability value of 0.0380 < 0.05.